2020
DOI: 10.5755/j01.ms.26.4.22329
|View full text |Cite
|
Sign up to set email alerts
|

Arc Characteristics and Weld Bead Microstructure of Ti-6Al-4V Titanium Alloy in Ultra-high Frequency Pulse Gas Tungsten Arc Welding (UHFP-GTAW) Process

Abstract: To resolve the problem of grain coarsening occurring in the fusion zone and the heat-affected zone during conventional gas tungsten arc welding(C-GTAW) welded titanium alloy, which severely restricts the improvement of weld mechanical properties, welding experiments on Ti-6Al-4V titanium alloy by adopting ultra-high frequency pulse gas tungsten arc welding (UHFP-GTAW) technique were carried out to study arc characteristics and weld bead microstructure. Combined with image processing technique, arc shapes durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Wang et al [9] quantitatively analyzed the ultrasonic acoustic flow phenomenon in arc plasma at ultrasonic frequency (20kHz~30kHz), revealed the promotion effect of ultrasonic on arc plasma concentration and acceleration. Li et al [10] showed that the heat input of high frequency pulse current was more concentrated. Kumar A. and Chen et al [11,12] analyzed the three-dimensional electromagnetic force through simulation, revealed that high-frequency current can increase arc pressure and promote molten pool flow.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [9] quantitatively analyzed the ultrasonic acoustic flow phenomenon in arc plasma at ultrasonic frequency (20kHz~30kHz), revealed the promotion effect of ultrasonic on arc plasma concentration and acceleration. Li et al [10] showed that the heat input of high frequency pulse current was more concentrated. Kumar A. and Chen et al [11,12] analyzed the three-dimensional electromagnetic force through simulation, revealed that high-frequency current can increase arc pressure and promote molten pool flow.…”
Section: Introductionmentioning
confidence: 99%